Expression and differential regulation of Id1, a dominant negative regulator of basic helix-loop-helix transcription factors, in glomerular mesangial cells. - Simonson, M S (1993)
Id is a family of dominant negative helix-loop-helix (HLH) proteins that block cell-specific transcription mediated by basic HLH (bHLH) transcription mediated by basic HLH (bHLH) transcription factors. We have analyzed Id1 expression in mesangial cells as a first step towards understanding the putative role of bHLH transcription factors in cell type-specific gene expression in the kidney. Glomerular mesangial cells expressed an abundant 1.1 kb mRNA transcript for Id1, but in contrast to other cell types Id1 mRNA was expressed in both randomly cycling cells and in serum-deprived, quiescent cultures. When quiescent mesangial cells were treated with serum to re-enter G1, Id1 mRNA levels were rapidly (2-4 h) and transiently down-regulated. Down-regulation of Id1 mRNA following addition of serum to mesangial cells was cell type-specific and contrasted with induction of Id1 by serum in BHK-21 and 3T3 fibroblasts. Down-regulation of Id1 mRNA correlated with mitogenesis and occurred when quiescent cells were treated with growth factors that activate G protein-coupled receptors and receptor protein tyrosine kinases but not with a non-mitogenic cAMP analog. Down-regulation of Id1 by growth factors required de novo protein synthesis, suggesting that a labile protein was involved. Appearance of E-box DNA binding activity in mesangial cell extracts followed down-regulation of Id1 message. Steady state Id1 mRNA levels and E-box DNA binding activity were not tightly correlated, suggesting complex regulation of Id1 activity. mRNA transcripts for E2A gene products were also expressed in mesangial cells, but these cells failed to express mRNAs for MyoA/MyoD-related genes. Collectively, these data demonstrate that Id1 is expressed in renal mesangial cells and suggest that bHLH complexes might be important for transcriptional regulation in the kidney. In addition, the observation that Id1 mRNA is transiently down-regulated by serum in mesangial cells suggests that Id1 gene expression is more complicated than previously appreciated and is tightly regulated in a cell-specific manner.